Journal of Settlements and Spatial Planning, vol. 9, no 1-2018 - ZOTIC, Vasile (2019)
The Journal of Settlements and Spatial Planning is the first scientific publication of the Centre for Research on Settlements and Urbanism, Babeș-Bolyai University, Faculty of Geography, Department of Human Geography and Tourism. Since 2010, this peer-review journal has been edited biannually in English focusing on interdisciplinary research on settlements and their spatial impact. Journal of Settlements and Spatial Planning seeks to publish original theoretical and applied research studies on a range of subjects addressed to urban and rural settlements and spatial planning, as well as precise issues related to both of them. Our journal addresses mainly to geographers, young researchers and also to other specialists in adjacent fields of research that focus their attention on aspects related to settlements and spatial planning. This journal has a high level of specialization: its basic research subjects are the socio-economic development of rural and urban settlements and related issues of spatial planning. The two major subject areas of the journal are relevant in the context of transition, globalization and exchange of values in society. By its thematic, this journal aims to become a bridging debate platform between geographers, architects and territorial planners.